The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/jo101372v
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Acylketene Formation? 1,3-Dioxin-4-ones via Silver(I) Activation of Phenylthioacetoacetate in the Presence of Ketones

Abstract: Silver (I) activation of thioacetoacetates in the presence of ketones produces 1,3-dioxin-4-ones. Mechanistic studies addressing the intermediacy of an acylketene intermediate are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…To date the most widely used approach involves the cycloaddition of imines to acyl ketenes, which are often generated in situ . Recent literature describes a method to generate such acyl ketenes under mild reaction conditions and has subsequently proved useful for the synthesis of oxazinones, but the inherent electronic requirements of cycloaddition chemistry remain. Other methods to access 1,3-oxazin-4-ones include palladium-mediated carbonylations of α-diazo-β-dicarbonyl compounds and condensation reactions between hydroxyl amides and various carbonyl-containing compounds .…”
Section: Introductionmentioning
confidence: 99%
“…To date the most widely used approach involves the cycloaddition of imines to acyl ketenes, which are often generated in situ . Recent literature describes a method to generate such acyl ketenes under mild reaction conditions and has subsequently proved useful for the synthesis of oxazinones, but the inherent electronic requirements of cycloaddition chemistry remain. Other methods to access 1,3-oxazin-4-ones include palladium-mediated carbonylations of α-diazo-β-dicarbonyl compounds and condensation reactions between hydroxyl amides and various carbonyl-containing compounds .…”
Section: Introductionmentioning
confidence: 99%
“…When we used NBS, 9 the starting material was consumed but complex mixture was obtained without the desired product (entry 3). While Cu( ii ) 10 a did not promote the intended reaction (entry 4), Ag( i ) 10 quickly converted the thioester and afforded the cyclized product with low yield (entry 5). This result seemed to be due to side reactions through ketene formation.…”
Section: Resultsmentioning
confidence: 99%
“…First considered were the electronic effects. The originally disclosed use of acyl-thioesters 12 by Hoye et al showed the capacity for their reaction with ketones in the presence of silver trifluoroacetate to generate 1,3-dioxan-4-enones . These reactions were performed in chloroform, at room temperature, over 1.5 h (cf.…”
Section: Results and Discussionmentioning
confidence: 99%